2011
DOI: 10.1172/jci57332
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus entry mediator regulates hypoxia-inducible factor–1α and erythropoiesis in mice

Abstract: Erythropoiesis, the production of red blood cells, must be tightly controlled to ensure adequate oxygen delivery to tissues without causing thrombosis or stroke. Control of physiologic and pathologic erythropoiesis is dependent predominantly on erythropoietin (EPO), the expression of which is regulated by hypoxia-inducible factor (HIF) activity in response to low oxygen tension. Accumulating evidence indicates that oxygen-independent mediators, including inflammatory stimuli, cytokines, and growth factors, als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In this context, it is important to emphasize that a deficiency in CD24 does not affect basal/homeostatic erythropoiesis and only diminishes (or more precisely delays) pathologic stress-induced erythropoiesis. Thus, it is likely that CD24 is only one of several, e.g., herpesvirus entry mediator (HVEM) (40) and acetate (41), stress sensors capable of regulating erythropoiesis in response to stress.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it is important to emphasize that a deficiency in CD24 does not affect basal/homeostatic erythropoiesis and only diminishes (or more precisely delays) pathologic stress-induced erythropoiesis. Thus, it is likely that CD24 is only one of several, e.g., herpesvirus entry mediator (HVEM) (40) and acetate (41), stress sensors capable of regulating erythropoiesis in response to stress.…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicated that LBH1 mAb abrogated not only LIGHT-HVEM interaction (18,25) but also BTLA-HVEM interaction (data not shown). Thus, we next examined whether LBH1 treatment ameliorated EAU by interfering with HVEM stimulatory cosignals.…”
Section: Amelioration Of Eau By Treatment With Antagonistic Anti-hvemmentioning
confidence: 58%
“…We previously developed an anti-HVEM mAb clone LBH1 that has antagonistic but not agonistic ability (18,25). Our data indicated that LBH1 mAb abrogated not only LIGHT-HVEM interaction (18,25) but also BTLA-HVEM interaction (data not shown).…”
Section: Amelioration Of Eau By Treatment With Antagonistic Anti-hvemmentioning
confidence: 68%
See 2 more Smart Citations